Experimental investigation of DI diesel engine emission characteristics using base metals as catalyst. (2022) - Sathiskumar, S.; Boopathi, M.; Sriram, K.; Sriram, T.; Shabesh, R.; Suga Prasanth, R.
Abstract: Despite the fact that there are numerous measures to reduce automotive emissions, the industry's constant manufacturing of automobiles serves as a critical deterrent to the dramatic increase in environmental pollution. The automobile industry contributes about 35% of Carbon monoxide, 30% of Hydrocarbon, and 25% of Nitrogen oxides to the environment, all of which are harmful to the environment. These compounds are hazardous to both the atmosphere and affect living organisms. In automobiles, a catalytic converter was designed to transform more hazardous pollutants into less hazardous pollutants in the exhaust gas. Because it was extremely effective and accurate at reducing hazardous exhaust emissions, this method was commonly accepted for use in vehicles. In the treatment of vehicle exhaust gases, several types of catalysts, such as noble metal and base metal catalysts are used. From this, base metals such as Cu, Mn, and Ni was selected as a catalyst because of their cost, high performance, and high catalytic activity. A single cylinder four-stroke VCR diesel engine with eddy current dynamometer was identified to carry out this experimental work. In this work, the experiment was conducted with five different loads by a honeycomb structure coated with copper, nickel and manganese as an oxidation and reduction catalyst. As per the outcomes of the experiments, it is observed that the reduction is 11%, 10%, and 10% for CO, HC, and CO2 where a slight increase in NOx for full load compared with without catalytic converter.